SPEECH ACT AND PRAGMATICS - Tuhtayeva Shahzoda Oktamovna. (Ta’lim innovatsiyasi va integratsiyasi, 2025)
Abstract: This article describes a language from variety of directions, using pragmatics and expression which serves to identify any thing, process, event, action.